2016
DOI: 10.1007/s00464-016-5095-3
|View full text |Cite
|
Sign up to set email alerts
|

How many samples would be optimal for endobronchial cryobiopsy?

Abstract: When the diagnostic benefits and complication rates were considered, two cryobiopsies were found to be optimal for endobronchial tumors. In patients with non-diagnostic conventional bronchoscopy, endobronchial tumors may be diagnosed by cryobiopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
1
8
1
Order By: Relevance
“…Several methods to grade the severity of bleeding have been reported in the literature [9,10,11,12,13,14]. However, argon plasma coagulation cannot be easily performed for bleeding from PPLs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods to grade the severity of bleeding have been reported in the literature [9,10,11,12,13,14]. However, argon plasma coagulation cannot be easily performed for bleeding from PPLs.…”
Section: Methodsmentioning
confidence: 99%
“…The attachment of a flexible cryoprobe to bronchoscopes was first reported in a study that examined its usefulness for eliminating tracheobronchial obstruction [5]. Since the latter half of the 20th century, cryobiopsy (CB) has been used for the diagnosis of diffuse lung diseases [6,7,8] and central lung cancers [9,10,11,12,13,14]. This technique enables the collection of much larger and more or less intact samples than FB.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rate of severe bleeding is comparable of forceps biopsy and cryobiopsy. In recently published, prospective study, two cryo biopsies was found to be optimal for diagnosis and greater than three bryobiopsies will increase the risk of bleeding (24). Cryotechnology has been a considerable choice for endobronchial lesion biopsy with better diagnostic yield and minimal complication.…”
Section: Tissue Sampling: Forceps Versus Cryotechnologymentioning
confidence: 99%
“…In this study, a 1.9 mm cryoprobe was used, and the specimen size is similar to that described in the literature but is larger than the forceps biopsy specimen size [ 3 ]. A previous study suggested that two cryobiopsies are optimal for endobronchial tumors [ 27 ], but the optimal number of cryobiopsies for peripheral lesions has not been determined. Recently, important issues regarding safety and standardization of transbronchial cryobiopsies were addressed [ 23 , 28 ].…”
Section: Discussionmentioning
confidence: 99%